Pengaruh Trust, Service Quality Dan Satisfaction Terhadap Repurchase Intention Pada Pengguna Online PT Great Seasons Travel Kota Batam - Pratama, Ryoland; Purba, Daris (SCIENTIA JOURNAL, 2021)
The aim of this study is to determine if there is an effect of trust, service quality and satisfaction on the repurchase intention of PT Great Seasons Travel Batam City online users with a total sample of 180 respondents. The data collection method used a questionnaire which was distributed directly, the data quality test in this research used validity and reliability tests, the classical hypothesis test and the influence test were performed in this study using multiple linear regression analysis and coefficient of determination (R2) analysis while for the hypothesis test on This study uses (t-test) and (f-test), which uses SPSS 25 software. The coefficient of determination (R2) obtained by the trust, servise and satisfaction variables is 79.1% of therepurchase intention variables. From the results of the t-test and the f-test, we can conclude from this study that there is a positive and significant effect on the variables of trust, service quality and Satisfaction on the repurchase intention , as well as on the significant influence between the three independent variables on the dependent variable